Systematic Literature Review on the Effectiveness, Methodological Trends, and Implementation Challenges of LEA-Based Flashcard Media for Early Reading and Writing Skills in Primary School - Aisya Widya Ulfa; Nurita Bayu Kusmayanti; Indra Jaya (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
Early reading and writing skills constitute the fundamental academic foundation that directly determines students' success across all disciplines throughout their educational journey. Nevertheless, Indonesia's literacy achievement remains critically concerning, as evidenced by its ranking of 68th out of 81 countries in the Programme for International Student Assessment (PISA) 2022. This condition underscores the urgent need for innovative, contextually grounded, and evidence-based instructional media. This study aims to systematically examine: (1) the effectiveness of LEA-based flashcard media in supporting early reading and writing skills; (2) methodological trends in relevant empirical studies; and (3) challenges in implementing LEA-based flashcard media in elementary school contexts. A Systematic Literature Review (SLR) employing the PRISMA protocol was conducted across Google Scholar, ERIC, Scopus, Garuda, and SINTA databases, covering publications from 2022 to 2025. Of 309 initially identified articles, 25 fulfilled all inclusion criteria and were subsequently analyzed thematically and descriptively through a quality appraisal process with inter-rater reliability of κ = 0.82. Findings consistently demonstrate that flashcard media integrated with Language Experience Approach principles contributes substantially to early reading and writing competencies, though its effectiveness is mediated by teacher pedagogical competence, learning environment quality, and contextual factors such as urban-rural disparities. Three principal themes emerged: the effectiveness of experience-based media on early literacy outcomes and its affective dimensions; the pivotal yet variable role of teachers' competence and systemic support in optimizing media implementation; and the critical importance of accurate, data-driven early assessment within diverse contextual constraints. This review concludes that LEA-based flashcard media development must be embedded within a comprehensive learning ecosystem that encompasses teacher capacity-building, active parental engagement, print-rich classroom environments, and educational policies genuinely responsive to the diverse social and cultural contexts of Indonesian students.